Pelvic injury and acute respiratory distress syndrome in the patients, suffering severe combined trauma - F. I. Ibrahimov (Клінічна хірургія, 2019)
Objective. Lowering of mortality in the patients, suffering severe combined pelvic injuries and acute respiratory distress-syndrome (ARDS), using a new tactics of treatment.